The social and political thought of Benedict XVI - Rourke, Thomas R. (Lanham, Md. : Lexington Books, 2010)
Covering the entire trajectory of his religious life, this meticulously researched book identifies the roots of political and social order in Pope Benedict XVI's philosophy and analyzes his views on the role of Christian faith in politics. Although not generally characterized as a political philosopher, the Benedict's writings shed significant and unique light on the world of politics today. In an age when modern politics has lost sight of its proper relationship within the larger scheme of human affairsand existence, Thomas R. Rourke shows that, as both Pope and the former Cardinal Ratzinger
Chapter 01. Introduction; Chapter 02. Anthropological Foundations; Chapter 03. Revelation, Reason, and Politics; Chapter 04. Special Topics; Chapter 05. Culture and Society; Chapter 06. Conclusion; Appendix: Caritas in Veritate; Selected Bibliography; Index; About the Author
Includes bibliographical references and index.
Description based on print version record.
Keywords: Benedict -- XVI, -- Pope, -- 1927-; Christianity and politics -- Catholic Church; Christian sociology -- Catholic Church; Catholic Church -- Doctrines; 1927-; Benedict; Catholic Church; Christian sociology; Christianity and politics; Doctrines; Pope; XVI; Religion; RELIGION -- Christianity -- General; RELIGION -- Christian Life -- Social Issues; Benedikt (Papst, XVI.); Soziologische Theorie; Politisches Denken; Katholische Soziallehre; Theologische Anthropologie; Geschichte 2005-2009; Electronic books